PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Lonardo, Felix; Tjakrawala, F.X. Kurniawan (Jurnal Paradigma Akuntansi, 2025)
Firm value affects productivity, influence, firm size and organizational capital design. This study aims to examine some of these factors observationally in food and drink area producer organizations that have been listed on the Indonesia Stock Exchange (IDX) in 2017 - 2021. 40 assembly organizations in the food and drink area have tried to take advantage of non-profability. inspection technique. The optional information used in this organization is the assembly organization's fiscal report. The specialist engaged the SPSS form 22 program in handling the information in this review. Specialists got the consequences of the inspection led as follows: productivity, company size, and capital construction significantly impact the benefits of assembling organizations in the food and beverage sector, while the influence significantly affects a value in the company.